2022
DOI: 10.1101/2022.01.19.476928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultra-flexible and Stretchable Intrafascicular Peripheral Nerve Recording Device with Axon-dimension, Cuff-less Microneedle Electrode Array

Abstract: Peripheral nerve mapping tools with higher spatial resolution are needed to advance systems neuroscience, and potentially provide a closed-loop biomarker in neuromodulation applications. Two critical challenges of microscale neural interfaces are (i) how to apply them to small peripheral nerves, and (ii) how to minimize chronic reactivity. We developed a flexible microneedle nerve array (MINA), which is the first high-density penetrating electrode array made with axon-sized silicon microneedles embedded in low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As introduced earlier, Yan et al 52 combined DRIE with silicone casting and backside alignment to fabricate a Utah-like stretchable 3D MEA. However, the process flow involves complex steps, which usually affect fabrication costs and device design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As introduced earlier, Yan et al 52 combined DRIE with silicone casting and backside alignment to fabricate a Utah-like stretchable 3D MEA. However, the process flow involves complex steps, which usually affect fabrication costs and device design.…”
Section: Discussionmentioning
confidence: 99%
“…Because the fabrication process of the USEA is based on wafer-etching, conventional 3D microelectrode arrays (3D MEAs) are based on rigid silicon as the substrate material 50 . However, Lee et al 51 and Yan et al 52 demonstrated the possibility of producing flexible Utah-like 3D MEAs with silicon pillars by combining several micromachining techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of flexible HDMEAs with these ideal properties entails confronting both the general challenges inherent to HDMEAs and specific challenges unique to their flexible design, encompassing mechanical (Oldroyd and Malliaras, 2022), electrical (Szostak et al, 2017;Qiang et al, 2021), biological (Golabchi et al, 2019), chemical (Shepherd et al, 2021), and interconnection issues (Behfar et al, 2021). In response, researchers employ strategies spanning material exploration (Bonafe, 2022;Chik et al, 2022), flexible HDMEA design innovation, advanced fabrication strategies (Scholten et al, 2020;Shah et al, 2022;Xiang et al, 2022), engineering optimization (Chik et al, 2022;Yan et al, 2022;Yin et al, 2022), and holistic combination strategies (Eunah et al, 2022;Hong et al, 2022), aiming to enhance performance and minimize risks in flexible neural interfacing devices.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the injection approach is accompanied by a risk of needle breakage and overdosing, and it eventually requires waste management of sharps (Yao et al, 2020). Microneedles (MNs) are devices with arrays of microscale needles or pins that can bypass the external barriers of tissues and achieve enhanced therapeutic delivery or biosensing in a minimally invasive manner (Byun et al, 2017; Yan et al, 2022) (Figure 1A–a,b). Various types of MNs, such as solid, hollow, or coated MNs, have been developed to increase the efficacy of MNs depending on their specific applications (Lee, Goudie, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%